2014
DOI: 10.1016/j.bjan.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes doses de esmolol sobre a resposta hemodinâmica, BIS e resposta de movimento durante a intubação orotraqueal: estudo prospectivo, randômico e duplo‐cego

Abstract: In clinical practise we believe that after 1mgkg(-1) loading dose, 150μgkg(-1)min(-1) iv esmolol dose is sufficient to suppress responses to tracheal intubation without increasing side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…Furthermore, another study has shown that a bolus injection of esmolol 1 mg/kg prior to intubation and continuous infusion at 150 μg/kg/min also resulted in blunted hemodynamic changes. [ 21 ] Overall, multiple studies with various designs have been performed thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study has shown that a bolus injection of esmolol 1 mg/kg prior to intubation and continuous infusion at 150 μg/kg/min also resulted in blunted hemodynamic changes. [ 21 ] Overall, multiple studies with various designs have been performed thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Desta maneira, a estreita relação entre taquicardia e isquemia do miocárdio sugeriu o uso de bloqueadores dos receptores β-adrenérgicos para a supressão da resposta hemodinâmica à intubação traqueal, como por exemplo o esmolol que é um antagonista cardiosseletivo do receptor ß1 de ação ultracurta 3 . É eficaz no embotamento das respostas aos estímulos adrenérgicos perioperatórios, incluindo intubação traqueal, eventos intraoperatórios causados pela diminuição da profundidade anestésica e extubação traqueal 4 .…”
Section: Introductionunclassified
“…No entanto, estudos revelam que o esmolol pode potenciar a redução das necessidades de anestésicos durante a anestesia com propofol ou inalatória. Além disso, sugeriu-se que a infusão de esmolol reduziu o uso intraoperatório de fentanil, diminuindo as respostas hemodinâmicas e reduziu o consumo de morfina no período pós-operatório 3 .…”
Section: Introductionunclassified
“…Laryngoscopy and tracheal intubation (TI) during anesthesia induction boost catecholamine release by sympathetic stimulation, which may lead to increased blood pressure (BP), heart rate (HR), and arrhythmia, and cause myocardial ischemia and infarction in patients with risk factors, such as high BP and ischemic heart disease. 1 2 Local anesthetics, beta receptor blockers, and opiates are thus used to prevent cardiovascular changes during intubation1 and some studies have shown that fentanyl, sufentanil, alfentanil, and other opioids prevent the changes induced by interventions with anesthesia. 3 4 5 6 …”
Section: Introductionmentioning
confidence: 99%